1993
DOI: 10.1111/j.1472-765x.1993.tb01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella viruses in diverse fresh waters in North East England

Abstract: Viruses, which infected strains of exsymbiotic Chlorella of European origin, were found in fresh waters in NE England. In contrast, an exsymbiotic Chlorella strain of N American origin, which is susceptible to viruses which are ubiquitous in US waters, was not infected by viruses from NE England waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
0
1
Order By: Relevance
“…Syngen viruses were the most abundant viruses in the urban lake; in contrast, no Pbi viruses were detected during the surveillance period. These results contrast with previous studies on the distribution of chloroviruses in inland waters in England, in which infectious SAG and Pbi viruses were present, but NC64A viruses were absent [35], suggesting a non-uniform worldwide distribution of chloroviruses in inland waters. Other studies that focused only on NC64A viruses indicated that they were common in various locations within the United States [16,17], China [18], Japan [20], Korea [21] and Australia (Van Etten, unpublished results) but absent in northern Europe (Van Etten, unpublished results).…”
Section: Chloroviruses Are Ubiquitous Throughout the Yearcontrasting
confidence: 99%
“…Syngen viruses were the most abundant viruses in the urban lake; in contrast, no Pbi viruses were detected during the surveillance period. These results contrast with previous studies on the distribution of chloroviruses in inland waters in England, in which infectious SAG and Pbi viruses were present, but NC64A viruses were absent [35], suggesting a non-uniform worldwide distribution of chloroviruses in inland waters. Other studies that focused only on NC64A viruses indicated that they were common in various locations within the United States [16,17], China [18], Japan [20], Korea [21] and Australia (Van Etten, unpublished results) but absent in northern Europe (Van Etten, unpublished results).…”
Section: Chloroviruses Are Ubiquitous Throughout the Yearcontrasting
confidence: 99%